2020
DOI: 10.1038/s41598-020-72489-3
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a stable transfection method in Babesia microti and identification of a novel bidirectional promoter of Babesia microti

Abstract: Babesia microti, an emerging human pathogen, is primarily transmitted through a bite of an infected tick and blood transfusions in human. Stable transfection technique has been reported in many protozoan parasites over the past few years. However, in vivo transient and stable transfection method has not been established for Babesia microti. Here, for the first time, we present a method of transient as well as stable transfection of the Babesia microti (B. microti) in the in vivo conditions. We have identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…However, until now, the in vitro cultivated system and gene manipulating methods of B. microti are not mature and it is difficult to confirm the direct involvement of Bm TLP in parasite invasion in vitro . Recently, two studies reported the establishment of transient or stable transfection method in B. microti and the discovery of a novel bidirectional promoter of B. microti ( Jaijyan et al., 2020 ; Liu et al., 2020 ), raising hope for gene-editing research in Babesia .…”
Section: Discussionmentioning
confidence: 99%
“…However, until now, the in vitro cultivated system and gene manipulating methods of B. microti are not mature and it is difficult to confirm the direct involvement of Bm TLP in parasite invasion in vitro . Recently, two studies reported the establishment of transient or stable transfection method in B. microti and the discovery of a novel bidirectional promoter of B. microti ( Jaijyan et al., 2020 ; Liu et al., 2020 ), raising hope for gene-editing research in Babesia .…”
Section: Discussionmentioning
confidence: 99%
“…This information is expected to set the stage for future research directed to understand the biology and pathogenicity of this parasite and to explore proteases as targets for developing novel therapeutic interventions. Recent advances in B. microti gene editing will permit exploring the functional relevance of selected proteases [89,90]. In addition, the application of computer-based inhibitor screening and the use of optimized pipelines to test drug efficacies using in vitro cultures and animal models allows obtaining new therapeutics against human babesiosis in a relatively short period of time [34,91,92].…”
Section: Discussionmentioning
confidence: 99%
“…However, hdhfr also confers resistance to pyrimethamine and this drug could be used instead of WR99210. These advancements in genetic manipulation of Babesia bovis genome inspired other scientists to establish transfection tools for several other Babesia Additionally, stable transfections were reported for several Babesia parasites including B. ovata, B. gibsoni, B. bigemina, and B. microti [41,[45][46][47]. As for most of these parasites, the availability of a robust in vitro culture system was a prerequisite to establishing the genetic tools.…”
Section: Genome and Genetic Tools For Babesiamentioning
confidence: 99%
“…As for most of these parasites, the availability of a robust in vitro culture system was a prerequisite to establishing the genetic tools. Regarding B. microti, although stable transfection has been reported in the in vivo condition, transgenic parasites were enriched using fluorescent-activated cell sorting [47]. It is needed to optimize drugs for the selection of transgenic parasites in future studies.…”
Section: Genome and Genetic Tools For Babesiamentioning
confidence: 99%